Urban Food Systems Governance and Poverty in African Cities - Battersby, Jane; Watson, Vanessa; Battersby, Jane; Watson, Vanessa (Taylor & Francis, 2018)
This book presents the findings of an international collaborative research project that aimed to improve our understanding of the connections between urban poverty, food systems, household food security and governance, by focusing on three secondary cities in Anglophone sub-Saharan Africa.
English
Keywords: Food & society; Central government; Urban & municipal planning; Food security; Food supply; Government policy; Poverty; Urbanization; Africa; Kenya; Kisumu; Kitwe